THE EFFECTIVENESS OF TWO-STAY TWO STRAY IN ENHANCING STUDENTS’ SPEAKING ABILITY - Andri Iswanto; Sela Anugrah (IKIP Siliwangi, 2020)
The study is aimed at describing the effectiveness of two stay and two stray in enhancing students’speaking ability. The paper is derived from the research result conducted among 30 students of SMK Budi Bakti Utama Padalarang. Classroom action research design with 2 cycles was applied to encourage students’ speaking skill. Observation checklist, fieldnote and speaking test instruments were used to catch on students’ progress (reflection and evaluation) . Observation was finished to see how clear the strategy was understood and performed by the leraners. Fieldnote aimed at jotting down success and restraint of the strategy usage and tes instrument was managed to assess the grading and scoring development whole the first and second cycles. Reflecting and evaluating were organized at the end of every cycle. Based on observation and fieldnote that the students’participation were getting upgraded in every cycle. Besides, the average score and grade at the end of 2 cycles were getting improved. Mean score of cycle 1 was 59.00, and cycle 2 was 65.00. It could be concluded that two stay and two stray strategy boosted speaking ability for English department students of SMK Budi Bakti Utama Padalarang in academic year 2018/2019.